Weaknesses in the protection of vulnerable persons undergoing clinical trials - Catalina Georgeta Dinu (Jus et Civitas, 2020)
The article seeks to highlight certain shortcomings at the legislative level in a certain area of health – clinical trials, referring to the protection of vulnerable patients and their rights. Conducting clinical trials on patients with mental illness raises several questions, in terms of obtaining Informed Consent. Thus, chronic patients with mental illness, that are hospitalized in medical units can be subjected to clinical tests for drugs for human use only in exceptional conditions, they are integrated into the category of vulnerable patients, which requires special care in terms of meeting the legal conditions for their participation in clinical trials performed. Are their protection mechanisms sufficient so that chronic patients understand the risks and consequences of participating in such tests?
Keywords: vulnerable patients; chronic mental disorders; clinical trial; informed consent; discernment